2002
DOI: 10.1046/j.1526-100x.2002.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Functional Performance of Juvenile Salmon Habitat in Recovering Wetlands of the Salmon River Estuary, Oregon, U.S.A.

Abstract: For an estuarine restoration project to be successful it must reverse anthropogenic effects and restore lost ecosystem functions. Restoration projects that aim to rehabilitate endangered species populations make project success even more important, because if misjudged damage to already weakened populations may result. Determining project success depends on our ability to assess the functional state or "performance" and the trajectory of ecosystem development. Mature system structure is often the desired "end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
109
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 26 publications
7
109
0
Order By: Relevance
“…Miller & Simenstad 1997, Mathieson et al 2000, Gray et al 2002, Barletta et al 2003, Bottom et al 2005. The fyke nets were composed of a 3.2 mm (1/8 inch) mesh mouth, body, and live trap in the cod end, as well as adjustable 6.4 mm (1/4 inch) mesh wings that attached to the net mouth and extended to the sides of each channel and to the marsh edge.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Miller & Simenstad 1997, Mathieson et al 2000, Gray et al 2002, Barletta et al 2003, Bottom et al 2005. The fyke nets were composed of a 3.2 mm (1/8 inch) mesh mouth, body, and live trap in the cod end, as well as adjustable 6.4 mm (1/4 inch) mesh wings that attached to the net mouth and extended to the sides of each channel and to the marsh edge.…”
Section: Studymentioning
confidence: 99%
“…The uppermost reaches of channel systems provide nursery grounds for early life stages of fishes, whereas downstream sections provide low-tide refuge for larger nekton using adjacent subtidal regions (Weinstein 1979, Rozas & Zimmerman 2000. First-order channels are highly productive, providing low predation pressure, reduced competition, diminished flow velocities, lower temperatures, and an extensive food supply for large numbers of juvenile fishes (Shenker & Dean 1979, Bozeman & Dean 1980, Rozas & Hackney 1984, Rozas & Odum 1987b, Gray et al 2002. Rozas et al (1988) found that small first-order channels (coined 'rivulets') contained a significantly higher biomass of fishes than larger adjacent channels and appeared to be the preferred pathway for marsh surface access.…”
Section: Introductionmentioning
confidence: 99%
“…These tidal restrictions result in altered hydrology and biogeochemistry, and degraded vegetation, nekton, and bird communities compared to unrestricted salt marshes (BURDICK et al, 1997;EERTMAN et al, 2002;GRAY et al, 2002;LLANSO, BELL, and VOSE, 1998;MYSHRALL et al, 2000;PORTNOY, 1991PORTNOY, , 1999PORTNOY and GIBLIN, 1997;RAPOSA, 2002;ROMAN, GARVINE, and PORT-NOY, 1995;ROMAN, NIERING, and WARREN, 1984;ROMAN et al, 2002;SINICROPE et al, 1990;VOSE and BELL, 1994;WARREN et al, 2002). Salt marshes are integral to the proper functioning of estuarine systems, and in recognition of the negative effects of tidal restrictions, efforts are now underway to restore tidal flow and ecological function to many of these degraded systems.…”
Section: Introductionmentioning
confidence: 99%
“…Salmon River estuary, located north of Lincoln City, Oregon, just south of Cascade Head Preserve, is approximately 800 hectares, half being emergent marshlands (Gray et al 2002). Since 1978, the US Forest Service (USFS) has completed a series of projects to remove dikes and tidal gates within the estuary, returning almost 70% of the historic wetlands to tidal inundation (Gray et al 2002).…”
Section: Study Sitementioning
confidence: 99%
“…Since 1978, the US Forest Service (USFS) has completed a series of projects to remove dikes and tidal gates within the estuary, returning almost 70% of the historic wetlands to tidal inundation (Gray et al 2002). Focal plots for this study were located on an island of low marsh, north of the main channel, at approximately river kilometer 1.6, in an area that had never been diked (Figure 3-1).…”
Section: Study Sitementioning
confidence: 99%